Analisis Dampak Sosial Media Terhadap Pendidikan Karakter Siswa Sekolah Dasar - MutiaraPuradireja, Syifa; Futri, Elmalia; Salsabilla, Maghfira; Wahyudin, Dede; Caturiasari, Jennyta (FKIP, PGSD, Universitas Slamet Riyadi, 2025)
The rapid development of technology and the lack of digital education for the community make all groups use social media freely without education. In this case, the concern is students who are still in elementary school and who are already using social media freely. This research uses a qualitative method with a case study type. The main data source in this research is news articles about elementary school children who are influenced by social media so that it has an impact on children's behavior and character education, which is sourced from online news portals on the internet regarding the case. The result of the discussion of this case is that the incident ended peacefully in a family manner. Beyond that, it certainly cannot be justified; even if it causes victims, it is the same as bullying, especially for the reason of going viral. Translated with DeepL.com (free version)